2022
DOI: 10.21873/cdp.10102
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pembrolizumab With Platinum-containing Chemotherapy for Pulmonary Enteric Adenocarcinoma

Abstract: Background/Aim: Pulmonary enteric adeno­carcinoma (PEAC) is a rare type of non-small cell lung cancer (NSCLC), for which no established standard treatment exists. Combination therapy with the anti-programmed cell death protein 1 antibody pembrolizumab and platinum-containing chemotherapy is the standard treatment for NSCLC patients, but its effectiveness in PEAC is uncertain. Case Report: We present a 68-year-old man with chemotherapy-naïve advanced PEAC who responded to a combination of pembrolizumab and plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A recently published case showed that a metastatic PEAC patient with a KRAS G12C mutation suffered hyperprogressive disease after one cycle of first-line paclitaxel plus carboplatin, along with sindilizumab ( 25 ). However, another recently published study demonstrated that primary and metastatic lesions were effectively treated by pembrolizumab plus carboplatin and pemetrexed in a PEAC with a KRAS G12D mutation ( 26 ). The discrepancy of clinical benefits between the two PEAC cases receiving first-line chemoimmunotherapy might be explained by the different NGS panels used and metastatic status, and the latter case received palliative radiation for bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published case showed that a metastatic PEAC patient with a KRAS G12C mutation suffered hyperprogressive disease after one cycle of first-line paclitaxel plus carboplatin, along with sindilizumab ( 25 ). However, another recently published study demonstrated that primary and metastatic lesions were effectively treated by pembrolizumab plus carboplatin and pemetrexed in a PEAC with a KRAS G12D mutation ( 26 ). The discrepancy of clinical benefits between the two PEAC cases receiving first-line chemoimmunotherapy might be explained by the different NGS panels used and metastatic status, and the latter case received palliative radiation for bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few reports exist on the response to chemotherapy (13)(14)(15)(16), this treatment regimen is generally considered unsuccessful (9). Notably, Tu et al ( 14) provided the only report on PEAC treated with chemoradiotherapy, and observed a partial response after four courses of pemetrexed (PEM) + cisplatin and 30 irradiation treatments.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to systemic therapy, Teranishi et al. ( 24 ) reported a 68-year-old male with a stage IV B diagnosis, positive KRAS G12D mutation, and a tumor percentage score (TPS) of <1% for programmed cell death ligand 1 (PD-L1). Palliative radiotherapy and pembrolizumab + pemetrexed + carboplatin chemotherapy were administered, and the outcome was evaluated as partial response (PR).…”
Section: Discussionmentioning
confidence: 99%